HOW TO MINIMIZE RISK: THE IMPLEMENTATION OF PUBLIC SECTOR SERVICES ELECTRONIC PROCUREMENT IN INDONESIA - Dodi Hardinata; Kamaludin Kamaludin (Jurnal Ilmiah Ekonomi Bisnis, 2022)
The trend of corruption cases in the types of goods and services procurement cases handled by the Corruption Eradication Commission of the Republic of Indonesia in 2004-2019 shows an increasing number in every year. In certain types of case studies the implementation of e-Procurement with e-Cataloq is proven to play a role in reducing the risk of corrupt practices in public organizations. The objectives of this research are to build an e-Procurement implementation model in Indonesia especially on electronic identity card procurement, identify external factors that encourage individuals to commit fraudulent behavior and the approval of procurement process of government goods and services. We operate a qualitative method with a case study on the implementation of e-Procurement of electronic identity cards. The results of the study explained that the implementation model of the procurement of goods and services using the e-Purchasing method through the e-Catalog mechanism is the best e-Procurement implementation model in the procurement of government goods and services specifically for the case of procurement of electronic identity cards.